Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00795-014-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubule morphology in rats with renal congestion: a study involving the in vivo cryotechnique

Abstract: The present study aimed to examine the changes induced in proximal tubules by renal congestion using the in vivo cryotechnique (IVCT). Twelve male Wistar rats were divided into four equal groups: group 1 (the control); groups 2 and 3, which were subjected to 2 and 5 min of congestion, respectively; and group 4, which was subjected to 5 min of congestion followed by 10 min of recirculation. Under anesthesia, renal congestion was induced in the bilateral kidneys by ligating the inferior vena cava just above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Moreover, the study of Zeier M et al (1998) documented that testosterone amplifies the compensatory growth of residual nephrons and such nephron hypertrophy may set the stage for accelerated progression of renal disease [35] . However, AAS induced PCT increased diameter and luminal debris detected in the present study could also be attributed to the observed congestion where Hemmi et al, (2015) stated that renal congestion was accompanied by an increase in diameter of PCT and obstruction of their lumina by swollen cells and ischemia-associated cell debris [36] .…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, the study of Zeier M et al (1998) documented that testosterone amplifies the compensatory growth of residual nephrons and such nephron hypertrophy may set the stage for accelerated progression of renal disease [35] . However, AAS induced PCT increased diameter and luminal debris detected in the present study could also be attributed to the observed congestion where Hemmi et al, (2015) stated that renal congestion was accompanied by an increase in diameter of PCT and obstruction of their lumina by swollen cells and ischemia-associated cell debris [36] .…”
Section: Discussionmentioning
confidence: 54%
“…Several authors considered that the tubules have a circular shape and therefore measured only one diameter [3][4][5][6][7][8][9][10]. However, our results showed that the convoluted tubules of the kidney are elliptical in shape; we measured a short diameter (the short axis of the ellipse) and a long diameter (the long axis of the ellipse) which differed significantly from each other (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 62%
“…However, there is no consensus in the literature on how tubular diameter (or diameters) should be evaluated. Several authors measure only one diameter, as if the tubules were circular [3][4][5][6][7][8][9][10]. On the contrary, other authors consider that the tubules have an elliptical shape and report the short diameter (minimum, proximal), sometimes along with the large diameter (maximum, distal) [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-established in rodent models of early CKD that in addition to glomerular hypertrophy, there is tubular hypertrophy. 14 Rodent models have primarily studied proximal tubules, [14][15][16][17][18] although a few have also evaluated distal tubules. 19,20 A study in human kidneys found that obese patients had a 54% larger cross-sectional area of proximal tubules than nonobese patients.…”
Section: Introductionmentioning
confidence: 99%